Total Knee Arthroplasty in Unrecognized Septic Arthritis-A Descriptive Case Series Study - Florian Hubert Sax; Bernd Fink (MDPI AG, 2023)
Background: Synovitis, like that associated with chronic bacterial arthritis, is a very rare finding during the implantation of knee endoprostheses. In such cases, we fix the knee prostheses with cement containing two antibiotics and carry out a course of systemic antibiotic administration. The aim was to analyze these cases for incidence, detection of bacteria, risk factors, and outcome. Methods: Out of 7534 knee replacements between January 2013 and December 2020, 25 cases were suspected during the surgical procedure to have suffered from bacterial arthritis and were treated accordingly. Total synovectomy was carried out, whereby five intraoperative synovial samples were examined bacteriologically, and the complete synovitis was analyzed histologically. The mean follow-up was 65.3 ± 27.1 (24-85) months. Results: In nine cases (0.12%), the diagnosis of bacterial arthritis was made histologically and by clinical chemistry (elevated CRP), and in two of these cases, pathogen verification was performed. Eight of these nine patients had previously had injections or surgery associated with the corresponding knee joint or had an underlying immunomodulatory disease. None of the patients developed a periprosthetic infection at a later stage. Conclusion: With an incidence of 0.12%, it is rare to unexpectedly detect bacterial synovitis during surgery. Total synovectomy, use of bone cement with two antibiotics, and immediate systemic antibiotic therapy seem to keep the risk of periprosthetic infection low.